2022
DOI: 10.3390/su14137902
|View full text |Cite
|
Sign up to set email alerts
|

Application of Cement Paste in Mining Works, Environmental Protection, and the Sustainable Development Goals in the Mining Industry

Abstract: Cement paste is an already well-known material used in ore mining. It is mainly used to fill excavation areas and the tailings from the surface return to underground mines. In this way, the amount of deposited material and degradation of the surface of the terrain are reduced. The paste itself can be used as an artificial barrier between mining works and underground watercourses. Significant economic and environmental benefits can be expected from using cement paste, which would contribute to sustainable devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The mining industry, with its tailings and acid mine drainage activities, is another source of waste with a very important negative impact on the environment and human health since it pollutes the surface and groundwater [21]. In their study, Ður devac Ignjatović et al revealed that other negative consequences of mining come from the use of heavy metals and radioactive elements, and the solution offered is the use of waste as backfill and the synthesis of paste with natural additives, which would result in better synthesized materials with lower negative impact against the groundwater.…”
Section: Context and Legal Frameworkmentioning
confidence: 99%
“…The mining industry, with its tailings and acid mine drainage activities, is another source of waste with a very important negative impact on the environment and human health since it pollutes the surface and groundwater [21]. In their study, Ður devac Ignjatović et al revealed that other negative consequences of mining come from the use of heavy metals and radioactive elements, and the solution offered is the use of waste as backfill and the synthesis of paste with natural additives, which would result in better synthesized materials with lower negative impact against the groundwater.…”
Section: Context and Legal Frameworkmentioning
confidence: 99%
“…Such change turns quite fruitful for the economy [2]; however, it rolls towards huge environmental concerns in some instances, and one of the most common is concrete waste management [3]. Construction activity generates waste from concrete as the base material [4], which, in substantial volumes, may become very dangerous for environmental sustainability and public health without proper management [5][6][7]. The present study hereby seeks to seek out and explain the factors, challenges, and possible pathways to enhance practices of waste concrete management in the construction industry of Pakistan [8].…”
Section: Introductionmentioning
confidence: 99%
“…explored material modification by adding waste rock, fiber, rod mill tailings, and cement to the tailings and identified the strength change pattern of tailings modified material with different mix ratios and the main factors affecting the strength. (Li et al, 2023), (Đurđevac Ignjatović et al, 2022), (Jin et al, 2022), (Hou et al, 2018), (Cui et al, 2020), (Kiventerä et al, 2019), (Wang et al, 2008;Wang et al, 2009) examined the influence law of admixtures (e.g., slag powder, quicklime, industrial gypsum, and bentonite) on tailings strength and recommended the optimal addition ratio. Temperature has a considerable effect on the strength growth of cured tailings because it influences the hydration of cement.…”
Section: Introductionmentioning
confidence: 99%